Impact of plastic mulch on soil microbial abundance, activity, and diversity in the saline-alkali soils of Xinjiang - Wu, Changxue; Zhang, Junxiao; Xu, Yongmei; Xie, Xiangwen (Frontiers in Microbiology, 2025)
IntroductionAs biodegradable plastic (BP) film gradually replaces traditional polyethylene (PE) film as an environmentally friendly alternative in agriculture, its impact on the soil microbial environment has attracted considerable attention.MethodsThis study examined the effects of different film coverings on the quantity, activity, and diversity of soil microorganisms by comparing fully biodegradable films with thicknesses of 0.01 mm and 0.012 mm to conventional PE films in typical cotton fields of Xinjiang.ResultsResults showed that the overall trends in microbial population dynamics were generally consistent across treatments. The abundance of bacteria and actinomycetes was highest under PE film, while fungi abundance peaked under the 0.012 mm BP film. With longer cultivation time, soil microorganisms exhibited a significant increase in total carbon source metabolism. Across the entire cotton growth period, different mulching treatments had only minor effects on microbial diversity. Both film cracking rates and the local environmental conditions emerged as key factors influencing the soil microbial community.ConclusionsConsidering the need for a low cracking rate during the seedling stage as well as soil environmental sustainability, BP film with a thickness of 0.01mm appeared to be the most suitable degradable option for practical use in cotton fields. Nevertheless, comprehensive evaluation of its long-term environmental benefits will require further research and sustained monitoring in conjunction with cotton growth.